2007
DOI: 10.1063/1.2779876
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulations of catanionic surfactants adsorbed at air/water interfaces. II. Full coverage

Abstract: We extend our previous molecular dynamics experiments ͓Rodriguez et al., J. Phys. Chem. B 109, 24427 ͑2005͔͒ to the analysis of the adsorption of catanionic surfactants at water/air interfaces, at a surfactant coverage close to that of the saturated monolayer: 30.3 Å 2 per headgroup. The mixture of surfactants investigated corresponds to equal amounts of dodecytrimethylammonium ͑DTA͒ and dodecylsulfate ͑DS͒. The structure of the interface is analyzed in terms of the local densities and orientational correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Moreover, limited studies on the interfacial behaviour of the IPAs at the air/water interface are available in literature. [15][16][17][26][27][28][29][30] Literature survey has been revealed that investigations on IPAs with systematic variation of the chain length of one of the components are only limited. 31,32 The study of Estoe et al 31 of aqueous solutions containing asymmetric chain catanionics of the homologous series n-propylammonium to n-heptylammonium dodecylsulphate (C 3 -C 12 to C 7 -C 12 ) has shown that the CMC of the catanionics decrease with increasing amine chain length where as the mean area per surfactant molecule and the mean area per hydrocarbon chain in the monolayer increase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, limited studies on the interfacial behaviour of the IPAs at the air/water interface are available in literature. [15][16][17][26][27][28][29][30] Literature survey has been revealed that investigations on IPAs with systematic variation of the chain length of one of the components are only limited. 31,32 The study of Estoe et al 31 of aqueous solutions containing asymmetric chain catanionics of the homologous series n-propylammonium to n-heptylammonium dodecylsulphate (C 3 -C 12 to C 7 -C 12 ) has shown that the CMC of the catanionics decrease with increasing amine chain length where as the mean area per surfactant molecule and the mean area per hydrocarbon chain in the monolayer increase.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Although different phases can be identified at the interface but their characteristic features and structures are still the subject of intensive research. Different techniques have been employed to study the phase behaviours and the interfacial morphologies of the IPAs; they are epifluorescence, polarization and Brewster angle microscopy, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Similar systems of interest include aqueous solutions [16][17][18]46 ͑the latter is a useful review on ion solvation at liquid surfaces͒ and surfactants at interfaces. [13][14][15]21 Surfactants will be usually located at the surface and most will reach the diffusive regime. The relationship between structure and dynamics is specially interesting in systems with strong profiling, such as liquid metals, 20 confined water, 22,23,25,27,28 and liquid-solid interfaces.…”
Section: -9mentioning
confidence: 99%
“…MD simulations have been widely used to investigate surfactant systems, however, sodium dodecyl sulphate (SDS) [28][29][30][31][32][33][34] or hexadecyltrimethylammonium bromide (CTAB) 29,35-38 have been investigated more extensively than sodium dodecylbenzene sulphonate (SDBS). Because of this, our chosen FF must be able to capture both the TS and SDBS and their mutual interactions, in the presence of water.…”
Section: Methodsmentioning
confidence: 99%
“…Because of this, our chosen FF must be able to capture both the TS and SDBS and their mutual interactions, in the presence of water. MD simulations have been widely used to investigate surfactant systems, however, sodium dodecyl sulphate (SDS) [28][29][30][31][32][33][34] or hexadecyltrimethylammonium bromide (CTAB) 29,[35][36][37][38] have been investigated more extensively than sodium dodecylbenzene sulphonate (SDBS). 33,39,40 Part of the reason for this may be ascribed to the very low critical micelle concentration (CMC) of SDBS, #3.0 mM under standard conditions, 41,42 compared with $8.3 mM for SDS, 42 meaning that the study of SDBS via simulation typically requires the simulation of systems comprising a large number of water molecules.…”
Section: Methodsmentioning
confidence: 99%